Managing Human Resources in Educational Libraries: The Role of Work Motivation and Work Environment in Enhancing Staff Performance - Hasyim Yusuf Alhasni; Andi Indriyani Ibrahim; Rosida P. Adam; Wisra Matalatta; Lindanur Sipatu (Journal of Educational Management Research, 2026)
This study aims to analyze the influence of work motivation and work environment on employee performance from the perspective of educational management, particularly in public libraries as non-formal educational institutions. Employee performance is a crucial element in educational management because it directly affects the quality of public services, learning resources, and literacy development in the community. This study uses a quantitative approach with a survey method. Data were collected through a structured questionnaire consisting of 25 items measured with a Likert scale and distributed to library employees. The data were analyzed using multiple regression analysis to test the partial and simultaneous effects of work motivation and work environment on employee performance. The results show that work motivation has a significant positive effect on employee performance, while the work environment also shows a significant influence in supporting employee effectiveness and productivity. Simultaneously, work motivation and work environment make a substantial contribution to improving employee performance. These findings imply that educational management in non-formal institutions should prioritize human resource management strategies, particularly through strengthening motivation systems and creating a conducive work environment, to improve organizational performance and support sustainable educational services.